Programma: 17 mei Senser, Nerve; 18-21 mei Drum Rhythm Festival; 22 mei A Girl Called Johnny; 23 mei Macka B & Robotniks & Mad Professor; 25 mei Nik Turner's, Space Ritual; 26 mei Toasters, The Regulators
Programma: 17 mei Senser, Nerve; 18-21 mei Drum Rhythm Festival; 22 mei A Girl Called Johnny; 23 mei Macka B & Robotniks & Mad Professor; 25 mei Nik Turner's, Space Ritual; 26 mei Toasters, The Regulators.